Peramalan Stok Semen di Gudang PT.Cemindo Gemilang Kuala Tanjung dengan WMA Method - Ega Mawarni; Adi Prijuna Lubis; Andy Sapta (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
PT Cemindo Gemilang is a company engaged in the distribution of cement, which is given the trademark Semen Merah Putih. Offices with cement collection warehouses have separate locations, one of which is located in Kuala Tanjung. Problems faced by PT. Warehouse. Cemindo Gemilang Kuala Tanjung is difficult to determine the cement that must be available for the next month. If inventory exceeds customer demand, storage costs will increase. The risk is that cement stored for too long will become hard so that it cannot be resold. Controlling inventory so that it is neither too much nor too little is very important. To maintain the continuity of the company, a cement inventory strategy is needed, namely by forecasting inventories in order to minimize the chance of losses. To be more efficient, the author designed a forecasting system using Visual Basic and MySQL database. The conclusion from the test results is that the forecasting accuracy value is 82% so that it can help PT. Cemindo Gemilang Kuala Tanjung Warehouse in making decisions in estimating cement supplies for the next period.